High-speed ADC-to-FPGA communication bandwidth optimization with link aggregator - Collado, J.; González, V.; Deltoro, J. M.; Gadea, A. (Frontiers in Detector Science and Technology, 2025)
In nuclear and high-energy physics experiments, data acquisition systems handle vast amounts of data from thousands of detectors and electronic channels, often reaching hundreds of terabits per second. While modern field programmable gate arrays (FPGAs) offer high-speed transceivers capable of processing such data, a mismatch can arise: individual analog-to-digital converters (ADCs) process lower data rates than FPGA transceivers can efficiently handle. This inefficiency leads to unnecessary usage of more powerful and expensive FPGAs, thus increasing system costs. This paper addresses this issue by proposing a link aggregator method for ADC readout. The solution integrates five universal link aggregator devices within an FPGA mezzanine card (FMC) board, enabling 1-to-1, 2-to-1, 3-to-1, or 4-to-1 multiplexing. The system optimizes FPGA resource utilization with support for up to 40 optical or copper inputs (2.5 Gbps per link) and a 10-line aggregated output (10 Gbps max) via a Vita57.1 FMC connector. A low-cost, low-power FPGA manages the mezzanine board as an intelligent standalone device. This approach significantly reduces hardware requirements and enhances cost-efficiency in high-performance data acquisition systems.